2020
DOI: 10.1021/acscatal.0c01536
|View full text |Cite
|
Sign up to set email alerts
|

AgPd and CuPd Catalysts for Selective Hydrogenation of Acetylene

Abstract: The selective hydrogenation of acetylene has been studied over AgPd and CuPd catalysts. Controlled surface reactions were used to synthesize these bimetallic nanoparticles on both TiO2 and SiO2 supports. Chemisorption measurements of the bimetallic catalysts indicate that Pd prefers to be on the nanoparticle surface with a Cu parent catalyst, while Pd prefers to be subsurface with a Ag parent catalyst. From energy-dispersive X-ray spectroscopy analysis, the composition of the nanoparticles is determined to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 78 publications
(174 reference statements)
2
92
5
Order By: Relevance
“…The presence of Cu in the surface is attested in the XAS results, which show a lower total coordination number on the Cu edge, compared to the Pd edge for the Pd3Cu and Pd1Cu1 samples. This result is in seeming contrast with the recent results of Ball et al [43], which show Pd preferentially segregated to the surface; we believe that this difference can be explained by the different particle size of the two catalysts. In the work of Ball et al [43], the catalyst particles are much smaller (~2 nm) than ours; we have shown in our previous work [19] that higher index planes, such as those found in smaller nanoparticles tend to stabilize surface Pd atoms, as opposed to surface Cu atoms.…”
Section: Resultscontrasting
confidence: 99%
“…The presence of Cu in the surface is attested in the XAS results, which show a lower total coordination number on the Cu edge, compared to the Pd edge for the Pd3Cu and Pd1Cu1 samples. This result is in seeming contrast with the recent results of Ball et al [43], which show Pd preferentially segregated to the surface; we believe that this difference can be explained by the different particle size of the two catalysts. In the work of Ball et al [43], the catalyst particles are much smaller (~2 nm) than ours; we have shown in our previous work [19] that higher index planes, such as those found in smaller nanoparticles tend to stabilize surface Pd atoms, as opposed to surface Cu atoms.…”
Section: Resultscontrasting
confidence: 99%
“…The presence of Cu in the surface is attested in the XAS results, which show a lower total coordination number on the Cu edge, compared to the Pd edge for the Pd3Cu and Pd1Cu1 samples. This result is in seeming contrast with the recent results of Ball et al [43], which show Pd preferentially segregated to the surface; we believe that this difference can be explained by the different particle size of the two catalysts.…”
Section: Scheme 1: Competing Reactions Selective Hydrogenation and Unselective Decarbonylation Routes Of Butyraldehydecontrasting
confidence: 99%
“…In the work of Ball et al [43], the catalyst particles are much smaller (~2 nm) than ours; we have shown in our previous work [19] that higher index planes, such as those found in smaller nanoparticles tend to stabilize surface Pd atoms, as opposed to surface Cu atoms. This may account for the observed difference in surface segregation.…”
Section: Scheme 1: Competing Reactions Selective Hydrogenation and Unselective Decarbonylation Routes Of Butyraldehydecontrasting
confidence: 45%
“…Meanwhile, for comparison, a Pd/SiO 2 catalyst with a particle size of 5.5±1.0 nm was also synthesized using the wet impregnation method (Figure S10), and then coated with different cycles of Ga 2 O 3 ALD (denoted as x cGa‐Pd/SiO 2 , Figure S11). We also synthesized the benchmark Pd 1 Ag/SiO 2 SAA catalyst by performing 3 cycles of Pd ALD on the Ag/SiO 2 catalyst followed by reduction at 500 °C in 10 % H 2 in Ar for 3 h. The particle size of Pd 1 Ag SAAs was about 4.0±0.6 nm (Figure S12a), and the SAA structure was confirmed by diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) CO chemisorption, where a peak at 2052 cm −1 , assigned to linear CO on isolated Pd atoms was only observed after the high temperature reduction (Figure S12b) [24] …”
Section: Figurementioning
confidence: 99%
“…To get an insight of the vast selectivity difference between Ga 2 O 3 ‐coated Ag@Pd and Pd samples as well as the much improved activity of Ga 2 O 3 ‐coated Ag@Pd than Pd 1 Ag SAA, in situ DRIFTS CO chemisorption measurements were carried out, since CO is a well‐known sensitive probe of Pd ensemble surface structures [24] . As shown in Figure 3 a, Pd/SiO 2 exhibited three CO vibrational peaks at 2095, 1967 and 1942 cm −1 , assigned to linear CO, bridge‐bonded CO on low‐coordination sites (eg.…”
Section: Figurementioning
confidence: 99%